Cidade, crise urbana e desenvolvimento sustentável City, Urban Crisis and Sustainable Development (Revista LIDER, 2020)
The research on public policies has become increasingly important because of its practical applicability, and the urgent need to overcome inequalities. This study systematizes the current debate on cities, urban process, sustainability, and the agendas of governance and sustainable territorial development.